A new phytotelmatic species of Monopelopia Fittkau, 1962 (Insecta: Diptera: Chironomidae: Tanypodinae) from South Brazil - Mendes, Humberto Fonseca; Marcondes, Carlos Brisola; de Pinho, Luiz Carlos (Zootaxa, 2003)
The new species Monopelopia caraguata sp. n. is figured and described. The material was collected in a bromeliad study in South Brazil – (Unidade de Conservação Ambiental Desterro – UCAD, Florianópolis, Santa Catarina State). A key to the Neotropical-Nearctic species is also provided.